Campaign 'Fill My Plate' in Increasing Knowledge and Habituation of Balanced Nutrition Patterns Among Students of SIT An Nahl Percikan Iman Jambi: Kampanye ‘Isi Piringku’ Dalam Meningkatkan Pengetahuan dan Pembiasaan Pola Gizi Seimbang Pada Siswa Sit An Nahl Percikan Iman Jambi - Sofiyetti, Sofiyetti; Rusdi, Mesa Sukmadani (Yayasan Ahmar Cendekia Indonesia, 2024)
This community service project is titled